Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

My question is as follows: What methods can be used to find the set of functions $f:\mathbb{R}\to\mathbb{R}$ satisfying a certain functional equation. An example of a case where this applies is the following:

Find all functions $f:\mathbb{R}\to\mathbb{R}$ which satisfy the following equation: $$f(x^{3})+f(y^{3})=(x+y)(f(x^{2})+f(y^{2})-f(xy)):\forall x, y\in\mathbb{R}$$

I'm curious as to whether there are general methods (or strategies) for solving this type of question, or whether questions like these should just be handled on a case-by-case basis.

Thanks in advance.

share|cite|improve this question
I believe that a case-by-case analysis is necessary. For example, it took a long time to find all solutions to the Cauchy Equation. I dont see how other cases would be simpler.'s_functional_equation – Ravi Jun 5 '12 at 15:35
@FortuonPaendrag Ahh, okay. I was just curious as to see whether there were general methods which I was not aware of that I could employ strictly for functions $f:\mathbb{R}\to\mathbb{R}$, it appears not. Thanks! – Shaktal Jun 5 '12 at 15:37
Also, since you need a form of the axiom choice to find many non-trivial solutions of Cauchy's equation, it makes it near-impossible to describe the solutions. Right now, I feel like you might have similar problems in your case. – Ravi Jun 5 '12 at 15:40
There are general strategies that are used by people looking at problems of this type in contests. Start by seeing what happens if you let one or both of $x$ and $y$ equal to $0$. Continue by exploring things like $y=-x$. Doing that in this question tells you that $f(-u)=-f(u)$, which is a nice start! – André Nicolas Jun 5 '12 at 15:45
Are you sure that you are not looking for continuous solutions? My approach would be trying to solve this for rational numbers and then use continuity. – Simon Markett Jun 5 '12 at 15:48
up vote 5 down vote accepted

Here is a typical start. Put $x=y=0$. The right side is $0$, so $f(0)=0$.

Now set $y=0$, and let $x$ roam freely. Since $f(0)=0$, we get $f(x^3)=xf(x^2)$.

Set $y=-x$. We get $f(x^3)+f(-x^3)=0$. Since everything is a cube, we have $f(-u)=-f(u)$ for all $u$.

Now explore $x=y$. Can we learn anything from setting $x$ and/or $y$ qual to $1$?

A little playing has gotten us a lot of information, enough that we should be able to complete things.

share|cite|improve this answer
Ahh; this is basically what I was looking for. Thank you. Are there any other common strategies which may also be applied to cases like this (not just this one specifically)? – Shaktal Jun 5 '12 at 16:02

Using the equation, we can see that $f(0) = 0$ is necessary. Let $y = -x$, then \begin{gather} f(x^3) + f(-x^3) = 0 \end{gather} This implies that $f$ must be an odd function. Also letting $y = x$ we see that \begin{equation} f(x^3) = x f(x^2) \end{equation} Plugging this relationship into the LHS gives \begin{align} xf(x^2) + yf(y^2) & = (x + y)(f(x^2) + f(y^2) - f(xy)) \\ 0 & = x f(y^2) + y f(x^2) - (x+y)f(xy) \tag{*} \end{align} If we let $y \to -y$ then by the symmetry of the function we have \begin{align} 0 = xf(y^2) - yf(x^2) + (x-y)f(xy) \tag{**} \end{align} Adding $(^*)$ and $(^{**})$ we see that \begin{equation} x f(y^2) = y f(xy) \end{equation} If we let $y = 1$ we obtain \begin{equation} f(x) = x f(1) \end{equation}

EDIT: At this point we should check whether this function indeed satisfies the above relation. Letting $f(1) = c$, and plugging in we have \begin{equation} c(x^3 + y^3) = c(x+y)(x^2 + y^2 - xy) = c(x^3 + xy^2 -x^2 y + x^2 y + y^3 - xy^2) = c(x^3 + y^3) \end{equation}

share|cite|improve this answer
Nicely done, except you must check if $f(x)=cx$ indeed works, for any constant $c\in\Bbb R$. You've only found a necessary condition, but not necessarily sufficient. – user26486 Jun 22 '15 at 0:56
@user26486 good point. Though is not straight forward enough to show that it is sufficient? – Gregory Jun 22 '15 at 1:02
Indeed, it's very straightforward. But you still should've mentioned it. It may happen it doesn't suffice. In an olympiad you'd probably lose a point for not checking it. – user26486 Jun 22 '15 at 1:04
Fair point. I will edit it. Thanks for the comment. – Gregory Jun 22 '15 at 1:47
The question was reasked in June '15, and merged with this one. Therefore this independent answer has a later date than the others. Please take that into account when voting. – Jyrki Lahtonen Jun 22 '15 at 11:24

If it is of any help the only continuous solutions are of the form $f(x)=xf(1)$. Indeed we can use the property $f(x^3)=xf(x^2)$ to show $$f(x)=x^\frac{1}{3}f(x^\frac{2}{3})=x^\frac{1}{3}x^\frac{2}{9}f(x^\frac{4}{9})=\cdots=x^{\frac13\sum_i(\frac23)^i}f(1)=xf(1).$$ In fact we only need continuity at $1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.